Pre-anesthesia evaluation in patients with chronic renal disease (emphasis on cardiovascular risk) (2013)
Chronic renal disease is a public health problem worldwide. Several times these patients will undergo surgical procedures related to dialysis or surgeries related to their co-morbidities. The purpose of the pre-anesthesia evaluation is to assess the risk of cardiovascular events and initiate interventions that may influence morbidity and mortality. This article describes the relevant epidemiological data of chronic kidney disease and its cardiovascular risk and provides a guide on clinical assessment, diagnostic tools and strategies to reduce surgical risk. This narrative literature review is based on articles written in both English and Spanish limited to the last 10 years, information from basic textbooks and primary databases (i.e., PUBMED - EMBASE - LILACS), supported by articles referenced in the above-mentioned search.